LAURA A. MILLAR, A Matter of Facts: The Value of Evidence in an Information Age - Klumpenhouwer, Tys (Archivaria, 2020)
A Matter of Facts: The Value of Evidence in an Information Age. Laura A. Millar. Chicago: ALA Neal-Schuman / Society of American Archivists, 2019. xix, 172 pp. ISBN 978-0-8389-1771-8